Pengaruh Foreign Branding dan Perceived Quality Terhadap Purchase Decision pada Produk Make Over Cabang Mall Ciputra Seraya Pekanbaru - Asyura, Bella; Othman, Lie (Universitas Respati Indonesia, 2025)
Purchase decisions are an important part of the marketing concept. This is the background to this research. Implementation of the brand strategy, namely good foreign branding and perceived quality provided by consumers because the quality provided by the company is good is part of the supporting factors for purchase decisions. This strategy is applied by PT Paragon Technology and Innovation to the Make Over brand. This research aims to determine the influence of Foreign Branding and Perceived Quality on Purchase Decisions on Make Over Products at the Ciputra Seraya Pekanbaru Mall Branch. The method used in this research is descriptive and quantitative, with research data sources coming from prime and secondary data. The number of samples in this research was 97 people with the sampling technique using purposive sampling technique. The analytical method for this research is multiple linear regression analysis and uses validity and reliability tests. In this research, the results obtained are that Foreign Branding (X1) has a positive and significant effect on Purchase Decision (Y), Perceived Quality (X2) has a positive and significant effect on Purchase Decision (Y), and Foreign Branding (X1) and Perceived Quality (X2 ) simultaneously influences the Purchase Decision (Y) on Make Over Products at the Ciputra Seraya Pekanbaru Mall.